Deontological Culture as a Basis of Acmeological Professional Competence of Family Doctor - Hlestova, Svetlana (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
Maturity of the professional competence of a family doctor in his morality, level of culture and the professionally of awareness. The comprehension of the deontological culture for a family doctor - is the path to his professional success. The object of attention of scientists it is problems of the formation and development of the professional culture of healthcare professionals (O. Krsek, M. Lisovoy, O. Uvarkina, J. Tsehmister etc.). Understanding of approaches to professional of deontology contributed to the labor G. Karahanovoy, K. Kertayevoy, A. Kuderinoy. Therefore, the purpose of Article substantiate the content and meaning «deontology of culture» to highlight the role and place of the deontological culture as acmeological basics of professional competence a family doctor in his upcoming practice. We consider namely deontological of culture it is the acmeological the basis professional competence of future of the family doctor, because it is this type of culture combines the set of professional and of moral values and qualities of future specialists. Summing up of the material presented of our study, we argue that deontology culture can become the acmeological basis professional competence of the family doctor only under such conditions as: continuous justification of the essence of deontological culture and its importance of for future professional activity of the family doctor during their studies at the university; introduction of ties deontological upbringing with professional practical activity of family doctors and their professional responsibilities; formation and development of deontological principles of family doctors as an inalienable constituent of professional knowledge etc